(untitled) (Research, Society and Development, 2021)
The south of Bahia has important remnants of the Atlantic Forest biome. There are two ways to preserve such remnants through conservation units and also through the cocoa production system (Theobroma cacao). The latter works under the native trees of the biome and faced a serious crisis, which began in the mid-1980s due to the negative trend of bulk cocoa prices in the international market and aggravated by the witches’ broom pest (Moniliophtora perniciosa), of considerable negative impacts either on the productivity of the cocoa crop and / or by the use of natural resources. Research was carried out in order to identify solutions in case of the introduction of cocoa clones more tolerant to the harmful Moniliophtora. However, the introduction of the AgroFlorestal System (SAF) in MAPES presented the potential to encourage cocoa production in farmers, because according to the economic modeling proposed by this article, it demonstrated an economic viability in the twenty-year time projection. In addition to the financial returns, which exceeded the cost rates of the Agroforestry System composed of cocoa (exotic species) and 52 other individuals of native species, there is the possibility of increasing the native vegetation of the Atlantic Forest biome.